2020
DOI: 10.1021/acs.jmedchem.0c00011
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Switch for Transforming a Purine Agonist for Toll-like Receptor 7 to a Clinically Relevant Antagonist

Abstract: Toll-like receptor 7 (TLR7) is an established therapeutic target in myriad autoimmune disorders, but no TLR7 antagonist is available for clinical use to date. Herein, we report a purine scaffold TLR7 antagonist, first-of-its-kind to our knowledge, which was developed by rationally dissecting the structural requirements for TLR7-targeted activity for a purine scaffold. Specifically, we identified a singular chemical switch at C-2 that could make a potent purine scaffold TLR7 agonist to lose agonism and acquire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…The result signifies that unsubstituted C-2 and C-8 positions, in addition to an additional basic center and an extended hydrophobic attachment at the C-6 and N-9 positions can be attributed to TLR7 antagonism. The structural evolution of the TLR7 agonist to the TLR7 antagonist is shown in Figure …”
Section: Structural Evolution: Structure–activity Relationship Develo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The result signifies that unsubstituted C-2 and C-8 positions, in addition to an additional basic center and an extended hydrophobic attachment at the C-6 and N-9 positions can be attributed to TLR7 antagonism. The structural evolution of the TLR7 agonist to the TLR7 antagonist is shown in Figure …”
Section: Structural Evolution: Structure–activity Relationship Develo...mentioning
confidence: 99%
“…The oxoadenine scaffold is extensively studied in the development of the TLR7 agonist through extensive SAR analysis, and this has led to the development of the clinical candidate GSK2245035 (Table 4) as a TLR7-specific agonist for the treatment of asthma. A study by Talukdar and coworkers 103 on the same scaffold revealed that a singular "chemical switch" can transform the molecule from a TLR7 agonist to a first-of-its-kind TLR7 antagonist. As previously discussed, (a) the alkyl-chain-like butoxy linker at the C-2 position and (b) the −NH 2 group at the C-6 position along with (c) substitution at the N-9 position are the prime requirements for the IFN-inducing property that leads to TLR7 agonism.…”
Section: Structural Evolution and Structure−activity Relationship Of ...mentioning
confidence: 99%
“…[113] This ability was demonstrated by a Talukar and co-workers, who identified a series of purine based ligands, whose interactions with the Toll-like receptor 7 (TLR7), could be agonistic (93) or antagonistic (94) depending on the presence of a butoxy chemical switch. [115] Figure 12. A) Portion of the X-ray co-crystal of compound 79 bound to phosphodiesterase-9 (PBD ID: 4Y87).…”
Section: Case Study: Functional Selectivity Agonism and Antagonismmentioning
confidence: 99%
“…[163] These compounds include approved, experimental and promising compounds which were discontinued late in the drug discovery process. Possibly the bestknown example of repurposing being successfully applied is that of the HIV-reverse transcriptase drug Zidovudine (115), which was first developed as a chain-terminating anticancer agent, that failed to progress due to poor in vitro activity in murine models of cancer. [164] The circumstances under which a compound may be useful for repurposing are varied, but simply put, it is either a function of the drug being capable of interacting with a different target or pathway (e. g., nelfinavir) or alternatively, the drugs original target and mechanism of action is important in another disease (e. g., duloxetine).…”
Section: Repurposingmentioning
confidence: 99%
“…The antimalarial agent hydroxychloroquine (HCQ), which operates as a nonselective endosomal TLR inhibitor, is widely utilized in the treatment of various autoimmune disorders [28]. Various researchers have reported molecules with quinazoline [29,30], benzoxazole [31][32][33], imidazopyridine [34,35], purine [36][37][38], and other varied scaffolds [39,40] that have been significantly investigated for the development of selective small-molecule TLR7 antagonists in several recent studies through empirical screenings and activity-guided strategies.…”
Section: Introductionmentioning
confidence: 99%